PERKECAMBAHAN BIJI ROTAN (Calamus caesius BLUME) DENGAN PERENDAMAN DALAM AIR KELAPA DAN GIBERELIN (GA3) - pardosi, immanuel kristian; Mukarlina, Mukarlina; Zakiah, Zulfa (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to determine the effect of coconut water and gibberellins on the germination of rattan seeds. The research design used was a completely randomized design with a factorial pattern consisting of 2 factors with 5 repetitions. The first factor (A) is coconut water consisting of control without coconut water 0% (A0), coconut water 25% (A1), coconut water 50% (A2), coconut water 75% (A3), and coconut water 100%(A4 ). The second factor is the concentration of gibberellins (GA3) consisting of control without gibberellins 0 ppm, 30 ppm (B1), 60 ppm (B2), and 90 ppm (B3). The results showed that coconut water and gibberellins had a significant effect on the percentage of germination, seedling height, number of roots, root length, and wet weight of rattan plants. A treatment combination of 75% coconut water and 90 ppm GA3 was the best treatment for the parameters of germination percentage (92,94%), seedling height (8,05cm), number of roots (4,06), root length (10,75cm), and wet weight rattan (5,04 grams).